2020
DOI: 10.1093/conphys/coz105
|View full text |Cite
|
Sign up to set email alerts
|

The endemic and endangered Maugean Skate (Zearaja maugeana) exhibits short-term severe hypoxia tolerance

Abstract: The endangered and range-restricted Maugean skate (Zearaja maugeana) is subjected to large environmental variability coupled with anthropogenic stressors in its endemic habitat, Macquarie Harbour, Tasmania. However, little is known about the basic biology/physiology of this skate, or how it may respond to future environmental challenges predicted from climate change and/or increases in human activities such as aquaculture. These skate live at a preferred depth of 5–15 m where the dissolved oxygen (DO) levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Indeed, currently available studies mostly feature acute (a few hours or less) or intermittent exposures (e.g., Rytkönen et al, 2012), which, similarly to early studies on high CO 2 effects, are not suitable for comparison with the remaining factors within the present framework. In fact, only two studies featured a sustained exposure to reduced levels of oxygen (Morash et al, 2020;Musa et al, 2020), one of them still fairly short in exposure duration (48H; Morash et al, 2020). While severely neglected, the effect of ED over elasmobranchs seems well within the range of the more well-studied EA.…”
Section: Stage I: General Responsementioning
confidence: 99%
“…Indeed, currently available studies mostly feature acute (a few hours or less) or intermittent exposures (e.g., Rytkönen et al, 2012), which, similarly to early studies on high CO 2 effects, are not suitable for comparison with the remaining factors within the present framework. In fact, only two studies featured a sustained exposure to reduced levels of oxygen (Morash et al, 2020;Musa et al, 2020), one of them still fairly short in exposure duration (48H; Morash et al, 2020). While severely neglected, the effect of ED over elasmobranchs seems well within the range of the more well-studied EA.…”
Section: Stage I: General Responsementioning
confidence: 99%
“…The middle layer is mixed. As Morash et al (2020) found out, the amount of dissolved oxygen at the skates’ preferred depths ranges from 90% saturation down to only 30% saturation; although, there are even areas with essentially no oxygen. Morash and her team wanted to know how the Maugean skate manages to swim around through all those different oxygen environments and how well it copes with even lower oxygen levels.…”
mentioning
confidence: 62%
“…Melanomacrophages are cells with phagocytic activity having a considerable number of dark pigments inside, like melanin, lipofuscin and hemosiderin. These Zearaja maugeana (Morash et al 2020). In all these studies, a commonly observed characteristic was the lack of changes in this parameter in response to different types of stressors.…”
Section: Discussionmentioning
confidence: 95%